2010
DOI: 10.1093/jigpal/jzq041
|View full text |Cite
|
Sign up to set email alerts
|

The logic of distributive bilattices

Abstract: Bilattices, introduced by Ginsberg [26] as a uniform framework for inference in Artificial Intelligence, are algebraic structures that proved useful in many fields. In recent years, Arieli and Avron [3] developed a logical system based on a class of bilattice-based matrices, called logical bilattices, and provided a Gentzen-style calculus for it. This logic is essentially an expansion of the well-known Belnap-Dunn four-valued logic to the standard language of bilattices. Our aim is to study Arieli and Avron's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…Its interest comes mainly from the fact that any interlaced pre-bilattice can be represented as a special product of two lattices. This result is well-known for bounded pre-bilattices, and it has been more recently generalized to the unbounded case [17,5]. The interlacing conditions may be strengthened through the following definition, due to Ginsberg [14].…”
Section: Algebraic Preliminariesmentioning
confidence: 95%
See 1 more Smart Citation
“…Its interest comes mainly from the fact that any interlaced pre-bilattice can be represented as a special product of two lattices. This result is well-known for bounded pre-bilattices, and it has been more recently generalized to the unbounded case [17,5]. The interlacing conditions may be strengthened through the following definition, due to Ginsberg [14].…”
Section: Algebraic Preliminariesmentioning
confidence: 95%
“…The interest in bilattices has thus different sources: among others, computer science and A.I. (see especially the works of Ginsberg, Arieli and Avron), logic programming (Fitting), lattice theory and algebra [16] and, more recently, algebraic logic [4,5,24]. An up-todate review of the applications of this formalism and also of the motivation behind its study can be found in the dissertation [24].…”
Section: Introductionmentioning
confidence: 99%
“…We then have ⊨ for all ∈ Γ and ∕ ⊨ , in other words, Γ ∕ ⊨ . 8 The asymmetry between the two definitions being exactly the "twist" in the twist-structure construction of Section V. Proof: Only a small adjustment is needed. By Theorem 9 we know that the algebraic countermodel is of the form ⟨B, 0 ⟩ where 0 is the least bifilter of B.…”
Section: Completenessmentioning
confidence: 98%
“…Given a modal bilattice B, one first defines an (equivalence) relation ≈ by letting ≈ if ∧ = ⊕ [8,Definition 3.7]. One then shows that the quotient B/≈ can be endowed with algebraic operations that turn it into a bimodal Boolean algebra: for…”
Section: Definition 11 a Bimodal Boolean Algebra Is A Structurementioning
confidence: 99%
“…Apart from mathematical logic ( [2,4,8,15,16,22,26,28]) and algebra, De Morgan algebras (and De Morgan bisemilattices) have applications in multi-valued simulations of digital circuits too ( [10,11]). …”
Section: Now Let Us Define De Morgan Algebras (Lattices)mentioning
confidence: 99%